Correlation Between Best Speaker Program Perception and Arabic Speaking Confidence of Naatiq International Arabiyyah Alumni - Lativa, Nurul; Nasrullah, M. Alaika (Study Program of Arabic Language Teaching, 2026)
This study aims to determine the relationship between the perception of Naatiq course alums of the Best Speaker program and their level of confidence in speaking Arabic at the Naatiq International Arabiyyah program. This research uses a quantitative, correlational design. The study population consisted of Naatiq course alumni from a single program period at Naatiq International Arabiyyah, with a sample of 45 respondents selected via simple random sampling. Primary data were collected through closed questionnaires (5-point Likert scale) from 45 Best Speaker alumni at Naatiq International Arabiyyah. Data collection was conducted through a closed-ended questionnaire using a five-point Likert scale to measure perceptions of the Best Speaker program and confidence in speaking Arabic. Data analysis included descriptive and inferential statistics, starting with normality and linearity tests as prerequisites, followed by the Pearson Product-Moment correlation test. The research results indicate a very strong, significant positive relationship between alumni's perception of the Best Speaker program and their level of confidence in speaking Arabic, with a correlation coefficient of r = 0.891 and a significance level of p < 0.01. This finding indicates that a positive perception of authentic speaking activities supported by a conducive learning environment contributes to increased confidence in speaking Arabic.